Subjective symptoms contributing to the quality of life of rheumatoid arthritis patients with clinical remission from the IORRA database. Issue 3 (2nd June 2022) - Sakai, Ryoko; Tanaka, Eiichi; Inoue, Eisuke; Sato, Minako; Tanaka, Masaru; Ikari, Katsunori; Yamanaka, Hisashi; Harigai, Masayoshi
ABSTRACT: Objectives: To explore patient-reported outcomes (PROs) related to quality of life (QOL) in patients with rheumatoid arthritis (RA) who achieved clinical remission. Methods: In the Institute of Rheumatology, Rheumatoid Arthritis dataset, RA patients >18 years old who met the simplified disease activity index (SDAI) remission criteria in April 2017 were enrolled in this analysis. Pain-visual analogue scale (pain-VAS) (0–100 mm), patient's global assessment of disease activity (Pt-GA; 0–100 mm), Japanese version of the Health Assessment Questionnaire, duration of morning joint stiffness, and fatigue [Checklist Individual Strength 8R (CIS)] were the tools used to evaluate PROs. To assess the contribution of each PRO to the European QOL-5 Dimensions-5 Level (EQ-5D-5L) score, an analysis of variance was conducted. Results: Among the 2443 patients with remission, the mean EQ-5D-5L was 0.9. The mean pain-VAS and Pt-GA were 7.2 and 7.4, respectively. Factors that significantly contributed to the EQ-5D-5L were pain-VAS (48.8%), CIS score (18.1%), and Pt-GA (15.6%). Around 82.5% of the variance in EQ-5D-5L was explained by the three PROs. Conclusions: This study demonstrated that pain-VAS, CIS, and Pt-GA were significant contributors to the EQ-5D-5L score in patients with RA who achieved the simplified disease activity index remission criteria.